Urgensi Perundang – Undangan Internasional Hague / Hague-Visby / Hamburg / Rotterdam oleh Indonesia - Anastasia Zefanya (Universitas Persada Indonesia YAI, 2023)
Many things are still being debated to ratify the law on the transportation of goods by seain Indonesia. International legislation is like the international agreement Hague / Hague-Visby /Hamburg / Rotterdam. These four conventions have been mostly implemented by most of the world'smaritime countries, leaving several countries to defend their versions, including Indonesia.Indonesia still adheres to the 1898 code inherited from the Dutch colonial era. The comparativeanalysis resulted in similar implementations of versions of the four UNCITRAL conventions adoptedby many countries. This strongly prompted Indonesia to replace the 1898 commercial code with thecurrent international practice that conveys Indonesia's best interests